Triterpenoids from Gymnema sylvestre and Their Pharmacological Activities - Giovanni Di Fabio; Valeria Romanucci; Anna De Marco; Armando Zarrelli (Molecules, 2014)
Because plants are estimated to produce over 200,000 metabolites, research into new natural substances that can be used in the pharmaceutical, agrochemical and agro-industrial production of drugs, biopesticides and food additives has grown in recent years. The global market for plant-derived drugs over the last decade has been estimated to be approximately 30.69 billion USD. A relevant specific example of a plant that is very interesting for its numerous pharmacological properties, which include antidiabetic, anticarcinogenic, and neuroprotective effects is Gymnema sylvestre, used as a medicinal plant in Asia for thousands of years. Its properties are attributed to triterpenoidic saponins. In light of the considerable interest generated in the chemistry and pharmacological properties of G. sylvestre triterpenes and their analogues, we have undertaken this review in an effort to summarise the available literature on these promising bioactive natural products. The review will detail studies on the isolation, chemistry and bioactivity of the triterpenoids, which are presented in the tables. In particular the triterpenoids oxidised at C-23; their isolation, distribution in different parts of the plant, and their NMR spectral data; their names and physico-chemical characterisation; and the biological properties associated with these compounds, with a focus on their potential chemotherapeutic applications.